Electrochemical characterization of the redox couple of [Fe(CN)6]3-/[Fe(CN)6]4- mediated by a grafted polymer modified glassy carbon electrode. - Radhi, Muhammed Mizher; Tan, Wee Tee; Ab. Rahman, Mohamad Zaki; Kassim, Anuar (The Society of Chemical Engineers, 2011)
A glassy carbon electrode (GCE) was modiﬁed with a grafted polymer GP ﬁlm (polystyrene grafted with acry- lonitrile as a monomer using gamma irradiation) using a solution evaporation method to produce a new modiﬁed electrode GP/GCE.The redox process of K3[Fe(CN)6] during cyclic voltammetry was studied using the GP/GCE. It was found that the peak separation (ΔEpa-c) between the redox peaks of ferricyanide ion in an aqueous solution is 82mV and the current ratio of redox peaks, (Ipa/Ipc), is 1 for the GP/GCE, indicating good reversibility with good conductivity of the modiﬁed electrode. Hence, it can be used for voltammetric analysis. The physical prop- erties of the modiﬁed electrode GP/GCE include good hardness, high adhesion to the metal surfaces of electrode collectors, solubility and good stability of the GP on GCE at different pH levels.Also, the sensitivity under condi- tions of cyclic voltammetry is signiﬁcantly dependent on the pH, the electrolyte used and the scan rate.At differ- ent scan rates, two oxidation peaks and two reduction peaks of Fe(III) were observed in a reversible process: Fe(III)/Fe(II) and Fe(II)/Fe(0).